AWARENESS AND SELF-PERCEPTION OF HALITOSIS AMONG UNDERGRADUATE STUDENTS AT UNIVERSITI BRUNEI DARUSSALAM. - ONG, Valen Jia Cin; KNIGHTS, Joe; Sher LIM, Lee; ABDUL RAHMAN, Hanif (Brunei International Medical Journal (BIMJ), 2024)
Introduction: Halitosis, or bad breath, is a prevalent health concern with social and psychological implications. This study investigated the knowledge of halitosis among undergraduate students at Universiti Brunei Darussalam (UBD), focusing on health-science (HS) and non-healthscience (non-HS) students. The research aimed to contribute to the understanding of halitosis within the context of undergraduate student populations and the impact of health science-based programmes. Methods: The study was conducted among 4108 undergraduate UBD students using a self-administered, closed-ended online questionnaire. Results: 279 students from five UBD undergraduate faculties participated in the study giving a response rate of 6.79%. HS students exhibited significantly higher awareness of factors contributing to halitosis, including smoking, tooth cavities, incorrect teeth cleaning, gastrointestinal tract disease, tonsillitis and certain medications. Furthermore, HS students reported receiving more educational material on halitosis (24.1% vs. 2.3%). Both HS and non-HS students primarily relied on dentists (62.0% vs. 56.1%) for halitosis consultations. In terms of self-perception, no significant difference was found between the two groups. The vast majority of students agreed that halitosis could negatively impact a person's life (92.8%). 49.1% of the respondents have been told that they have bad breath and felt embarrassed. Conclusion: The greater level of halitosis-related knowledge in HS students indicates the positive impact of HS programs and the potential need for educational initiatives among non-HS students. Halitosis presents a potentially significant issue in the sample, reflecting the relevance of its physical and psychological impact. Broader research with larger and more diverse samples is necessary to improve generalisability.